Some New Ostrowski-Type Inequalities Involving σ-Fractional Integrals - Bandar B. Mohsen; Muhammad Uzair Awan; Muhammad Zakria Javed; Muhammad Aslam Noor; Khalida Inayat Noor (Journal of Mathematics)
The aim of this paper is to derive some new fractional analogues of Ostrowski-type inequalities involving bounded functions using the concept of σ-Riemann–Liouville fractional integrals.